The Use of Meta-analysis in Management Science - Walecka, Anna; Zakrzewska-Bielawska, Agnieszka (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The paper discusses meta-analysis and its uses in management science. The first part presents the essence of the method, its main characteristics and its various stages as a procedure, with particular emphasis on the effects of different measures it uses. The next part of the paper introduces selected examples of the use of meta-analysis to examine problems in management science. Three of them are discussed in detail, each with a different aim for adopting this method. The summary indicates the main limitation of the use of meta-analysis as a research method and describes the direction of its methodological development.